2021
DOI: 10.25259/sni_38_2021
|View full text |Cite
|
Sign up to set email alerts
|

Ocular neuromyotonia caused by a recurrent sphenoidal ridge meningioma

Abstract: Background: Ocular neuromyotonia (ONM) is a rare ocular motility disorder characterized by involuntary paroxysmal extraocular muscle contraction and is caused by radiation therapy, vascular compression, and inflammatory disease. This study includes a rare case of ONM caused by a recurrent meningioma. Case Description: A 56-year-old man presented with diplopia due to the right oculomotor nerve palsy caused by a sphenoidal atypical meningioma, with improved symptoms after initial surgery. During the next 7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…No recurrence in 5 years. Read and Williams, 2017 [15] Cervicomedullary junction Neck pain and rapid onset of arm and leg weakness 5 years 1,4 cm enhancing mass at cervicomedullary junction WHO grade I Systemic doxorubicin n/a Sadiya et al , 2019 [16] Left frontal Slurred speech 1 year 2,9 × 2,5 × 2,4 cm solid cyctic tumor of left frontal dural base with invasion of brain parenchyma WHO grade II-III Subtotal resection and radiotherapy n/a Shingai et al , 2021 [17] Sphenoid Intermittent diplopia 7 years Tumor mass in the posterior part of sphenoid with right oculomotor invasion WHO grade II Resection and gamma knife radiotherapy n/a Thomas et al , 2019 [18] Right middle fossa Generalized tonic-clonic seizures 7 years, 2 years, 5 years, and 2 years 2,4 × 2,9 × 1,5 cm right middle fossa with foramen ovale invasion WHO grade II Surgical resection, bevacizumab and everolimus n/a Wang et al , 2015 [19] Right orbitofrontal Serious Headache, Gradually impaired vision of the right eye, and vomiting 3 years, 2 years, and 5 months 1. Small local reccurence tumor 2.…”
Section: Discussionmentioning
confidence: 99%
“…No recurrence in 5 years. Read and Williams, 2017 [15] Cervicomedullary junction Neck pain and rapid onset of arm and leg weakness 5 years 1,4 cm enhancing mass at cervicomedullary junction WHO grade I Systemic doxorubicin n/a Sadiya et al , 2019 [16] Left frontal Slurred speech 1 year 2,9 × 2,5 × 2,4 cm solid cyctic tumor of left frontal dural base with invasion of brain parenchyma WHO grade II-III Subtotal resection and radiotherapy n/a Shingai et al , 2021 [17] Sphenoid Intermittent diplopia 7 years Tumor mass in the posterior part of sphenoid with right oculomotor invasion WHO grade II Resection and gamma knife radiotherapy n/a Thomas et al , 2019 [18] Right middle fossa Generalized tonic-clonic seizures 7 years, 2 years, 5 years, and 2 years 2,4 × 2,9 × 1,5 cm right middle fossa with foramen ovale invasion WHO grade II Surgical resection, bevacizumab and everolimus n/a Wang et al , 2015 [19] Right orbitofrontal Serious Headache, Gradually impaired vision of the right eye, and vomiting 3 years, 2 years, and 5 months 1. Small local reccurence tumor 2.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of ONM as reported in the literature include hypovitaminosis D [3], congenital [22], alcohol ingestion [23], Paget disease of bone [24], myelogram with thorium toxicity [25], cavernous sinus thrombosis secondary to mucormycosis [26], intramedullary stroke [27], chronic inflammatory demyelinating disease [28], botulinum toxin injection [29], brainstem demyelination [30], Tolosa-Hunt syndrome [31], idiopathic [32], intracranial tumor [33], and as a presenting sign of meningioma [34].…”
Section: Pathogenesismentioning
confidence: 99%
“…In cases of ONM due to nerve compression, neurosurgical microvascular decompression can achieve resolution of symptoms. In a review of eight ONM cases with a clear relationship to nerve compression, Shingai et al found that placing a sponge between the nerve and the vessel resulted in improvement for all three of its cases while carbamazepine only resulted in improvement for two of its five cases [33].…”
Section: Treatmentmentioning
confidence: 99%